2007
DOI: 10.1007/s12035-007-0004-3
|View full text |Cite
|
Sign up to set email alerts
|

Cannabinoids and Neuroprotection in Basal Ganglia Disorders

Abstract: Cannabinoids have been proposed as clinically promising neuroprotective molecules, as they are capable to reduce excitotoxicity, calcium influx, and oxidative injury. They are also able to decrease inflammation by acting on glial processes that regulate neuronal survival and to restore blood supply to injured area by reducing the vasoconstriction produced by several endothelium-derived factors. Through one or more of these processes, cannabinoids may provide neuroprotection in different neurodegenerative disor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
1
6

Year Published

2008
2008
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 82 publications
(68 citation statements)
references
References 77 publications
(121 reference statements)
2
59
1
6
Order By: Relevance
“…Among these previous studies, the evidence revealing an elevation in CB1 receptor expression is supportive of a view that a general overactivity of CB1 receptors and their endocannabinoids are an event that develops when the degeneration of nigral dopaminergic neurons has progressed to a certain degree and that major parkinsonian symptoms are already evident [13]. Furthermore, as for our study, the present findings of [ 3 H] SR141716A binding down-regulation with 6-OHDA lesion are likely an event that occurs during the early phases of the PD rodent model [13,42]. Previous studies (7) 6-OHDA treated with high simvastatin have identified that the dopaminergic dysfunction rather than cell death occurs at the same time as CB1 receptors malfunction, which is likely due to the close interactions between dopaminergic and cannabinergic system that are manifested.…”
Section: Cb1 Receptor Binding Was Down-regulated In the 6-ohda-inducesupporting
confidence: 90%
“…Among these previous studies, the evidence revealing an elevation in CB1 receptor expression is supportive of a view that a general overactivity of CB1 receptors and their endocannabinoids are an event that develops when the degeneration of nigral dopaminergic neurons has progressed to a certain degree and that major parkinsonian symptoms are already evident [13]. Furthermore, as for our study, the present findings of [ 3 H] SR141716A binding down-regulation with 6-OHDA lesion are likely an event that occurs during the early phases of the PD rodent model [13,42]. Previous studies (7) 6-OHDA treated with high simvastatin have identified that the dopaminergic dysfunction rather than cell death occurs at the same time as CB1 receptors malfunction, which is likely due to the close interactions between dopaminergic and cannabinergic system that are manifested.…”
Section: Cb1 Receptor Binding Was Down-regulated In the 6-ohda-inducesupporting
confidence: 90%
“…Targeting of the CB1 receptor is useful for reducing bradykinesia and delaying L-dopa-induced dyskinesia (52). Various studies have reported the anti-inflammatory activity of CB1-receptor antagonists (53 -55) in animal models but the anti-neuroinflammatory activity of these molecules has not been evaluated with respect to neuroinflammatory disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Use of anti-inflammatory therapy for reducing the harmful effects of microglia has been proposed based on numerous studies (Craft et al, 2005;Skaper, 2007). Selective CB2 receptor agonists, which lack psychotropic properties, are one class of anti-inflammatory agents that have therapeutic potential in reducing inflammation associated with chronic conditions such as Alzheimer's disease and multiple sclerosis, as well as acute CNS injury such as OXIDATIVE METABOLISM OF ANANDAMIDE BY CYTOCHROME P450S stroke and trauma (Carrier et al, 2004;Maresz et al, 2005;Ortega-Gutiérrez et al, 2005;Ramírez et al, 2005;Fernández-Ruiz et al, 2007;Sagredo et al, 2007). The anandamide product 5,6-EET-EA could be an endogenously produced mediator that can alter microglial activity.…”
Section: E Cytochrome P450-mediated Anandamide Oxidation and Centralmentioning
confidence: 99%